2019
DOI: 10.3847/1538-4357/ab4c2e
|View full text |Cite
|
Sign up to set email alerts
|

Probing Structure in Cold Gas at z ≲ 1 with Gravitationally Lensed Quasar Sight Lines

Abstract: Absorption spectroscopy of gravitationally lensed quasars (GLQs) enables study of spatial variations in the interstellar and/or circumgalactic medium of foreground galaxies. We report observations of 4 GLQs, each with two images separated by 0.8-3.0 , that show strong absorbers at redshifts 0.4 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 123 publications
(169 reference statements)
2
14
0
Order By: Relevance
“…Multi-sightline information on the CGM of single galaxies has been obtained in a few cases from binary or multiple (two to four) grouped QSOs behind foreground galaxies (e.g., Bechtold et al 1994;Martin et al 2010;Keeney et al 2013;Bowen et al 2016), gravitationally lensed quasars (e.g., Smette et al 1992;Rauch et al 2001;Ellison et al 2004;Lopez et al 2005;Zahedy et al 2016;Rubin et al 2018;Kulkarni et al 2019), giant gravitational arcs (e.g., Lopez et al 2020), or extended bright background objects observed with integral field units (e.g., Péroux et al 2018). These observations provide better constraints on the kinematic relationship between the CGM gas and the galaxy and on the size of CGM structures.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-sightline information on the CGM of single galaxies has been obtained in a few cases from binary or multiple (two to four) grouped QSOs behind foreground galaxies (e.g., Bechtold et al 1994;Martin et al 2010;Keeney et al 2013;Bowen et al 2016), gravitationally lensed quasars (e.g., Smette et al 1992;Rauch et al 2001;Ellison et al 2004;Lopez et al 2005;Zahedy et al 2016;Rubin et al 2018;Kulkarni et al 2019), giant gravitational arcs (e.g., Lopez et al 2020), or extended bright background objects observed with integral field units (e.g., Péroux et al 2018). These observations provide better constraints on the kinematic relationship between the CGM gas and the galaxy and on the size of CGM structures.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-sightline information on the CGM of single galaxies has been obtained in a few cases from binary or multiple (2-4) grouped QSOs behind foreground galaxies (e.g., Bechtold et al 1994;Martin et al 2010;Keeney et al 2013;Bowen et al 2016), gravitationally-lensed quasars (e.g., Smette et al 1992;Rauch et al 2001;Ellison et al 2004;Lopez et al 2005;Zahedy et al 2016;Ru-bin et al 2018;Kulkarni et al 2019), giant gravitational arcs (e.g., Lopez et al 2020), or extended bright background objects observed with integral field units (e.g., Péroux et al 2018). These observations provide better constraints on the kinematic relationship between the CGM gas and the galaxy and on the size of CGM structures.…”
Section: Introductionmentioning
confidence: 99%
“…On smaller scales, gravitationally lensed background objects provide multiple images as background sources to study the material in absorption (e.g. Rauch et al 2001;Ellison et al 2004;Lopez et al 2007;Chen et al 2014;Rubin et al 2018;Kulkarni et al 2019). Such observations allow us to determine the coherence scale which is the length scale over which the gas traced by Ly𝛼 or metals does not vary.…”
Section: Introductionmentioning
confidence: 99%